Arachnoid Cysts - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A study of 67 childhood arachnoidal cysts is reported from the Service of Pediatric Neurology, Hospital "La Paza", Paseo de la Castellana, Madrid, Spain.